Maracas River, Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co.[Trinidad and Tobago], 2011)
The postcard shows some villagers doing laundry and bathing by the Maracas River. Postcard number 16069.
Colour: Black and white; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rivers--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. Joseph; Laundry--Trinidad and Tobago; Work; Laundresses--Trinidad and Tobago